Anti-inflammatory Therapies for Coronary Heart Disease: A Systematic Review and Meta-Analysis - Wang, Haiming; Jiang, Min; Li, Xin; Zhao, Yunzhang; Shao, Junjie; Liu, Zifan; Lin, Lejian; Xu, Qiang; Wang, Lin; Lu, Xuechun; Zhang, Haomin; Chen, Yundai; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Anti-inflammatory therapy has been proposed as a promising treatment for coronary heart disease (CHD) that could reduce residual inflammation risk (RIR) and therefore major adverse cardiovascular events. We implemented a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the clinical benefits of anti-inflammatory agents in patients with CHD based on secondary cardiovascular prevention. Methods: We systemically searched the PubMed, Embase, and Cochrane Library databases for RCTs (published between Jan 1, 1950, and June 1, 2021; no language restrictions) that focused on anti-inflammatory therapy for coronary heart disease. Our primary end points of interest were a composite of all-cause death, recurrent myocardial infarction and stroke. We processed pooled data using a random-effects model. Results: Of 1497 selected studies, 18 studies with 67,449 participants met our inclusion criteria and were included in the present meta-analysis. Comparing anti-inflammatory agents with placebo, there was no significant decrease in risk of primary end points, secondary end points, all-cause mortality, cardiac mortality, recurrent myocardial infarction, stroke or revascularization. Further subgroup analysis indicated that anti-inflammatory agents led to a significant reduction in secondary end points (OR 0.87, CI 0.77–0.99; P = 0.03), recurrent myocardial infarction (OR 0.86, CI 0.78–0.95; P = 0.003) and revascularization (OR 0.81, CI 0.70–0.92; P = 0.001) in patients with stable CHD compared with placebo. Moreover, stable CHD patients had a lower propensity for recurrent myocardial infarction than acute coronary syndrome (ACS) patients when using anti-inflammatory agents (P = 0.03). The colchicine subgroup analysis showed that colchicine yielded a promising reduction in the primary end points (OR 0.81, CI 0.70–0.95; P = 0.009) compared with placebo. Anti-inflammatory agents were associated with a higher risk of infection (OR 1.13, CI 1.03–1.23; P = 0.007) and negligible effects on cancers (OR 0.98, CI 0.90–1.06; P = 0.61). Conclusion: Anti-inflammatory agents appear to have beneficial effects in reducing the risk of recurrent myocardial infarction in patients with stable CHD, albeit at the cost of increased infection. Notably, colchicine demonstrates a promising cardioprotective effect with a lower incidence of major cardiovascular events and thus is a potential therapeutic strategy for stable CHD patients. Systematic Review Registration: PROSPERO, identifier CRD42021245514.